2014
DOI: 10.1107/s1600576714007912
|View full text |Cite
|
Sign up to set email alerts
|

In situX-ray diffraction study of point defects in neptunium dioxide at elevated temperature

Abstract: High-temperature X-ray diffraction measurements have been performed on neptunium dioxide up to 2000 K for the first time under He, He/5%H2and air atmospheres. Up to 1643 K, NpO2remains stoichiometric under all the considered atmospheres, and the coefficients of thermal expansion have been evaluated. Above 1643 K, the lattice parameter departs from linearity towards higher values. The atomic displacement parameters of the O and Np atoms were determined from Rietveld refinement and the Debye temperature subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…On the contrary, previous experimental studies reported abrupt increase of specific heat due to formation of Frenkel pairs and order-disorder pre-melting transitions [51][52][53][54][55].…”
Section: Melting Temperatures Of (Thu)o2 and (Thpu)o2 Moxmentioning
confidence: 60%
See 1 more Smart Citation
“…On the contrary, previous experimental studies reported abrupt increase of specific heat due to formation of Frenkel pairs and order-disorder pre-melting transitions [51][52][53][54][55].…”
Section: Melting Temperatures Of (Thu)o2 and (Thpu)o2 Moxmentioning
confidence: 60%
“…Fink et al [25] estimated the specific heat Cp(liquid) to be 61.76 J K the formation of oxygen defects, and in particular of Frenkel pairs, leads to an abrupt increase of the heat capacity as temperature approaches the melting point [51,52]. In the case of UO2 and ThO2, even a pre-melting order-disorder ''lambda'' transition has been proposed by certain authors [53][54][55].…”
Section: From Our MD Calculated H(t)-h(300) Versus Temperature Datamentioning
confidence: 99%
“…Consequently, as the drift from linearity observed as a function of temperature tends towards greater values of the lattice parameter of the fluorite structure, the materials studied are progressively reduced, i.e. their O/M ratio decreases (Chollet et al, 2014;Epifano et al, 2016Epifano et al, , 2017Vauchy, Belin, Robisson & Hodaj, 2016). As this drift increases with the americium content, one can expect that, at a given temperature, the greater the americium content, the lower the O/M ratio.…”
Section: Lattice Parameters At Elevated Temperaturesmentioning
confidence: 99%
“…In some materials, the structural damage generated by decay can lead to a complete amorphization of the material (Walter et al, 2007;Vigier et al, 2019). Furthermore, the self-irradiation generally induces a significant lattice swelling over time (Turcotte, 1976;Weber, 1984;Baclet et al, 2007;Thiebaut et al, 2007;Ravat et al, 2007;Nishi et al, 2013;Lebreton et al, 2014, (Baena et al, 2015) 5.47127 ( 8) (Leinders et al, 2015) 5.434 (1) (Chollet et al, 2014(Chollet et al, , 2012 5.39819 (1) (Belin et al, 2004) 5.3755 ( 5) (Vauchy et al, 2017) 5.593 (3) (Horlait et al, 2012) 5.4702 (4) (Yamashita et al, 1997) 5.4338 (3) (Yamashita et al, 1997) 5.3954 (4) (Yamashita et al, 1997) 5.375 (1) (Epifano et al, 2017(Epifano et al, , 2016 5.5974 (6) (Yamashita et al, 1997) 5.470 (Markin & Street, 1967) 5.4328 (2) (Fahey et al, 1974) 5.3953 (4) (Noe & Fuger, 1974) 5.3733 (Fahey et al, 1974) 5.5972 (5) (Zachariasen, 1948) 5.4704 (1) (Baldock et al, 1966) 5.434 (Sudakov et al, 1973) 5.3960 (3) (Ellinger, 1961) 5.377 (3) (Zachariasen, 1949) Figure 12 Experimental lattice parameters of the fluorite structure of ThO 2 , UO 2 , NpO 2 , PuO 2 and AmO 2 obtained in this study compared with the values in the literature from Table 2. 2016; Vigier et al, 2018).…”
Section: Figurementioning
confidence: 99%